موقف نصر حامد أبو زيد من تأسيس الأيديولوجية الوسطية للإمام الشافعي - M. Riza Budima; Saiful Ulum (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
The term wasat }iyah is always related to kindness, justice and balance. When juxtaposed with “ideology” the term becomes “ideology wasat} iyah,” meaning a way or idea of   thinking that is good and fair with an Islamic perspective. But an Egyptian modernist wrote a book entitled, “Al-Imam> al-Syafi>’i wa Ta’sīs al-Idiulūjiyyah al-Wasati}yah.” The author of this book is Nasr Hamid Abu Zaid, and everything written in his book contains criticism of Imam Syafi’i. Based on that the writer wants to make the book as an object of research that will be focused on Nasr Hamid Abu Zayd’s criticism of Imam Syafi’i from the aspect of wasat}iyah ideology. This study aims to counter Nasr Hamid’s criticisms of Imam Syafi’i. The author focuses his study on four aspects criticized by Nasr Hamid Abu Zayd to Imam Shafi ‘,   namely al-Qur’an, Sunnah, Ijma and Qiyas from the standpoint of wasati}yah ideology. The result is that the writer found that Nasr Hamid was wrong in evaluating Imam Syafi’i.